PUBLIC DIPLOMACY AS AN EFFECTIVE MECHANISM OF THE FOREIGN POLICY OF THE STATE - Іванова, Н. С. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2018)
The phenomenon of «public diplomacy» and its importance for the foreign policy of the state are researched. Considerable attention is paid to considering public diplomacy as a means of establishing long-term relationships that create favorable conditions for state policy. The importance of introducing the practice of public diplomacy in Ukraine in order to defend national interests and promote a positive international image of the state is grounded.